Nonlinear saturation of toroidal Alfvén eigenmodes via ion induced scattering in nonuniform plasmas - Zhiwen Cheng; Kexun Shen; Liu Chen; Fulvio Zonca; Zhiyong Qiu (Nuclear Fusion)
In nonuniform plasmas, toroidal Alfvén eigenmode (TAE) is shown to decay into high toroidal mode number modes due to ion induced scattering (Cheng et al 2024 Nucl. Fusion 64 066031). In this work, the three wave parametric decay model is generalized into reactor-relevant multiple-mode case, and the wave-kinetic equation describing the TAE spectrum evolution in k _θ space due to ion induced scattering is derived. Here, k _θ is the poloidal wavenumber. By numerically solving the wave-kinetic equation with reactor-relevant parameters, the nonlinear evolution and saturation process of TAE spectral intensity is derived, which yields a saturation spectrum consistent with the fixed point solution. It is found that the magnetic perturbation amplitude induced by the TAE saturation spectrum is lower than the uniform plasma result due to the enhanced nonlinear coupling by plasma nonuniformity. Potential impact on intrinsic plasma rotation is also discussed.